Ocean Thermal Energy Conversion : Technology Brief - Ruud, Kempener; Frank, Neumann (International Renewable Energy Agency IRENA, 2014)
This brief examines ocean thermal energy conversion (OTEC) technologies, one of the key methods for tapping renewable energy from the world's oceans.